Extracellular low‐n oligomers of tau cause selective synaptotoxicity without affecting cell viability. Issue 11 (18th May 2017) - Kaniyappan, Senthilvelrajan; Chandupatla, Ram Reddy; Mandelkow, Eva‐Maria; Mandelkow, Eckhard
Abstract: Introduction: Tau‐mediated toxicity in Alzheimer's disease is thought to operate through low‐n oligomers, rather than filamentous aggregates. However, the nature of oligomers and pathways of toxicity are poorly understood. Therefore, we investigated structural and functional aspects of highly purified oligomers of a pro‐aggregant tau species. Methods: Purified oligomers of the tau repeat domain were characterized by biophysical and structural methods. Functional aspects were investigated by cellular assays ((3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide) assay of cell viability, lactate dehydrogenase release assay [for cell toxicity], reactive oxygen species production, and calcium assay), combined with analysis of neuronal dendritic spines exposed to oligomers. Results: Purified low‐n oligomers are roughly globular, with sizes around 1.6 to 5.4 nm, exhibit an altered conformation, but do not have substantial β‐structure. Treatment of primary neurons with oligomers impairs spine morphology and density, accompanied by increased reactive oxygen species and intracellular calcium, but without affecting cell viability (by (3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide) assay of cell viability and lactate dehydrogenase release assay [for cell toxicity]). Discussion: Tau oligomers are toxic to synapses but not lethal to cells. Highlights: A novel purification method allows to characterize exclusively Tau RDΔK oligomers. Tau RDΔK oligomers have a distinct conformation but do not attain β‐sheet structure. Tau RDΔK oligomers cause severe synaptotoxicity without affecting cell viability. Tau RDΔK oligomers affect calcium homeostasis and increase ROS production. Tau RDΔK oligomers do not cause missorting of endogenous Tau, unlike Aβ oligomers.